Evaluasi Drug Related Problems (DRPs)Potensial pada Pasien Hipertensi di Instalasi Rawat Inap RS "Y" Periode Tahun 2015 - Hutama, Tifan Adji, Dra. Nurul Mutmainah, M.Si., Apt (2016)
Hypertension is the state of the blood pressure in the blood vessels chronically elevated. Hypertension in certain conditions leads to various complications such as kidney, heart and brain disease. Complications of hypertension causes the patient requires many medication for other indications, so that can cause drug-related problems. Potential drug-related problems can cause disruption of therapy so that treatment goals can not be maximized. The study was conducted with the aim of knowing the potential drug-related problems in patients with hypertension include drug interactions and innapropriateness of drug choices include the innapropriateness combination of antihypertensive drugs and effectiveness of antihypertensive drug but unsafe in hospitalized hypertensive patients at "Y" Hospital period of 2015. Research conducted an observational study with a non-experimental with collect the medical data records retrospectively by descriptive analysis. Samples were taken from a population of hospitalized patients with hypertension at "Y" Hospital period of 2015. It was found 80 samples of patients with purposive sampling method. There were 80 samples of patient's medical record collected with purposive sampling method who could potentially undergo drug interactions were 70 patients (90.00%) with 330 cases and a number of innapropriateness of drug choices were 21 patients (26,25%) with 21 cases. Innapropriatness combination of drug criteria found in 14 patients (17,5%) and effective drugs but unsafe found in 7 patients (8.75%).